Should We Go Organic? - Kate Welch; Linda Bobroff; Amy Simonne (EDIS)
“Choosing what to feed my family is no easy task. In addition to seeking meals that can be ready for our harried schedules and differing tastes, today when I go to the grocery store I also have to make decisions about whether or not to buy organically grown or raised foods. Many consumers worry that pesticides used in conventionally grown produce may increase our risk of cancer. But is this concern based in reality?” This 2-page fact sheet was written by Kate Welch, Linda Bobroff, and Amy Simonne, and published by the UF Department of Family, Youth and Community Sciences, August 2012.